2012
DOI: 10.1016/j.neuroscience.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex and chronic neonatal nicotine treatment on Na2+/K+/Cl− co-transporter 1, K+/Cl− co-transporter 2, brain-derived neurotrophic factor, NMDA receptor subunit 2A and NMDA receptor subunit 2B mRNA expression in the postnatal rat hippocampus

Abstract: Chronic exposure to nicotine during the first postnatal week in rats, a developmental period that corresponds to the third trimester of human gestation, results in sexually dimorphic long-term functional defects in the adult hippocampus. One potential cause could be the sex-specific differences in the maturation of GABAA receptor-mediated responses from excitatory to inhibitory, which depends on the expression of the Na2+/K+/Cl−-co-transporter NKCC1 and the K+/Cl− co-transporter KCC2. In the rat hippocampus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 72 publications
0
31
0
Order By: Relevance
“…Damborsky and Winzer-Serhan (2012) reported neonatal male rats have higher hippocampal Bdnf gene expression in dentate, CA1 and CA3 subregions at PN5, but not PN8. This is largely consistent with our observations with the exception of CA3, where we did not detect sex differences.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Damborsky and Winzer-Serhan (2012) reported neonatal male rats have higher hippocampal Bdnf gene expression in dentate, CA1 and CA3 subregions at PN5, but not PN8. This is largely consistent with our observations with the exception of CA3, where we did not detect sex differences.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to long-standing interest in the role of BDNF in hippocampal plasticity and neurogenesis in adults, particularly with regard to effects of estrogen, far fewer studies have examined BDNF expression in the developing hippocampus. Damborsky and Winzer-Serhan (2012) reported that neonatal male rats have higher hippocampal BDNF gene expression in dentate, CA1, and CA3 subregions at PN5, but not PN8. This is largely consistent with our observations with the exception of CA3, where we did not detect sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…As previously outlined, immature neurons have a high intracellular concentration of Cl − and GABA induces a depolarizing effect via GABA A Rs. A transition occurs in early development that alters Cl − co-transporters, resulting in greater extracellular Cl − concentrations and enables the activation of GABA A Rs to induce a hyperpolarizing effect (Payne et al, 1996;Rivera et al, 1999;Ben-Ari, 2002;Galanopoulou, 2008;Damborsky and Winzer-Serhan, 2012). The expression of these co-transporters occur at different times in males and females, which results in an earlier hyperpolarizing effect of GABA A Rs in females as compared to males (Nunez and McCarthy, 2007;Galanopoulou, 2008;Damborsky and Winzer-Serhan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine exposure during the early neonatal period of hippocampal maturation induces increased expression of the KCC2 cotransporter in male pups, a change that may influence the timing of the switch in GABA transmission from excitatory to inhibitory (Figure 3; Damborsky and Winzer-Serhan 2012). The long-term consequence of neonatal nicotine exposure is enhanced excitation in the adult hippocampal CA1, which is greater in males than females (Damborsky et al 2012).…”
Section: Early Sexual Differentiation Nachrs and Perturbation By Nimentioning
confidence: 99%